2001
DOI: 10.1603/0022-2585-38.2.180
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Survival of ImmatureHaematobia irritans(Diptera: Muscidae) is Influenced by Bacteria Isolated from Cattle Manure and Conspecific Larvae

Abstract: Twenty species of bacteria were isolated from cattle manure and seven species were isolated from the gut of larval horn fly Hematobia irritans (L.). Bacteria in manure belonged to the Bacillaceae, Pseudomonadaceae, Micrococcaceae, Corynebacteriaceae, Enterobacteriaceae, Microbacteriaceae, and two unassigned genera. Gut bacteria belonged to the Enterobacteriaceae, Bacillaceae, Neisseriaceae, and Pseudomonadaceae. H. irritans larval survival and growth on the various bacterial species were evaluated by rearing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 11 publications
3
33
0
1
Order By: Relevance
“…Several studies on the signiÞcance of bacterial interactions with muscoid ßies, such as house ßies, Musca domestica L. (Zurek et al 2000); stable ßies, Stomoxys calcitrans (L.) (Lysyk et al 1999, Romero et al 2006; and horn ßies, Hematobia irritans (L.) (Perotti et al 2001), reported some symbiotic relationships during larval development and also an oviposition attractant (in stable ßies). Ahmed et al (2006) identiÞed several species of bacteria, including Providencia spp.…”
mentioning
confidence: 99%
“…Several studies on the signiÞcance of bacterial interactions with muscoid ßies, such as house ßies, Musca domestica L. (Zurek et al 2000); stable ßies, Stomoxys calcitrans (L.) (Lysyk et al 1999, Romero et al 2006; and horn ßies, Hematobia irritans (L.) (Perotti et al 2001), reported some symbiotic relationships during larval development and also an oviposition attractant (in stable ßies). Ahmed et al (2006) identiÞed several species of bacteria, including Providencia spp.…”
mentioning
confidence: 99%
“…M (%) MC (%) C o n t r o l e 3 7 , 5 0 3 6 , 7 0 2 0 , 0 0 2 3 , 7 0 3 3 , 3 (SCHMIDTMANN & MARTIN, 1992;PEROTTI et al, 2001;ROMERO et al, 2006). Logo, para que um fungo possa atuar sobre os estágios imaturos de moscas, este deve possuir mecanismos que promovam elevada patogenicidade ou que anulem os fatores antimicrobianos do inseto.…”
Section: Methodsunclassified
“…The nature of this symbiosis is unclear. The significance of bacteria for the development of larvae has been examined for house flies [5][6][7], stable flies [8,9], horn flies [10], and face flies [11]. Digestibility of bacteria in the intestinal tract was demonstrated in house flies [12], stable flies [13], and blow flies [14,15].…”
Section: Nutrition and Developmentmentioning
confidence: 99%